(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Crops and agricultural products are the two main components of the agricultural sector. Plants are grown for a variety of food, industrial and other uses and have their own specific needs and care. Agricultural products include plant and animal products harvested in time.